Carbon-supported metal oxide material as well as preparation method and application thereof
By using cattail velvet fibers and doping nitrogen and phosphorus elements, and introducing oxygen vacancy on the surface of carbon-loaded metal oxide materials combined with reduction self-oxidation method, the problem of insufficient conductivity and specific surface area of biomass carbon-based electrocatalytic materials is solved, and its electrocatalytic performance is significantly improved.
Patent Information
- Application Number
- CN202510385335.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-28
- Publication Date
- 2025-06-27
AI Technical Summary
The insufficient conductivity and specific surface area of biomass carbon-based electrocatalytic materials lead to insufficient exposure of active sites, poor surface wetting, weak interface binding force between metal oxides and carbon matrix, and slow catalytic kinetics.
Cattail velvet fiber is used as the carbon source, and oxygen vacancy is introduced on the surface of the material through nitrogen and phosphorus doping and reducing self-oxidation to form a conductive network with a high specific surface area to improve the hydrophilicity and catalytic properties of the material.
It significantly improves the conductivity, structural stability and wettability of the material, improves the catalytic activity of the oxygen evolution reaction, reduces the reaction energy barrier, and achieves better electrocatalytic performance.
Smart Images

Figure CN120210858A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and specifically to a carbon-supported metal oxide material, a preparation method thereof, and an application thereof. Background Art
[0002] With the continuous growth of global energy demand, the sustainability issues of traditional fossil fuels and their environmental damage have become increasingly prominent. Developing renewable energy has become the key. Hydrogen energy has attracted much attention due to its high energy density and environmental friendliness. Among them, the hydrogen production technology by electrolyzing water has great potential because of its easily available raw materials and pollution-free characteristics. However, the oxygen evolution reaction (OER) in the electrolysis of water has become a technical bottleneck due to its slow kinetics. Layered double metal hydroxides exhibit excellent OER catalytic activity due to their unique layered structure and abundant active sites, and have important application value and research significance.
[0003] As non-precious metal materials gradually come into view, layered double metal hydroxides, as an alternative to noble metal catalysts, have also attracted people's attention. To realize layered double metal hydroxides as electrocatalytic materials, the most crucial issue lies in solving problems such as poor conductivity and limited number of active edge sites. From a performance perspective, electrocatalytic materials for the oxygen evolution reaction should have characteristics such as a high specific surface area, abundant active sites, and fast electron transport. Currently, the surface wettability of biomass carbon-based materials is poor, which limits the penetration of the electrolyte and the ion transport efficiency; the structure of layered double metal hydroxides is unstable and the conductivity is poor, which limits their catalytic efficiency.
[0004] After retrieval, Chinese Patent Publication No.: (CN105845451A) discloses a method of growing carbon nanotubes (CNTs) on a plant fiber substrate by CVD method and loading metal oxides. Although this method improves the conductivity of the electrode, it requires a high-temperature CVD process and does not involve element doping and oxygen vacancy construction, resulting in limited charge transfer efficiency.
[0005] Chinese Patent Publication No.: (CN103332677A) combines plant fibers with metal salts by a hydrothermal method to prepare a biomass carbon-based composite material. However, its carbon structure is disordered porous carbon with a low specific surface area (<300m 2 / g), and no heteroatom doping is introduced. The metal oxides are prone to agglomeration, and the OER overpotential is relatively high (>275 mV).
[0006] The above technologies have the following problems:
[0007] The conductivity and specific surface area of the biomass carbon substrate are insufficient, which limits the exposure of active sites; the surface wettability is poor, which limits the penetration of the electrolyte and the ion transport efficiency; the interfacial binding force between the metal oxide and the carbon matrix is weak; the lack of regulation of the electronic structure of the material (such as doping, defect engineering) leads to slow catalytic kinetics. Summary of the Invention
[0008] Aiming at the deficiencies of the prior art, the present invention provides a carbon-supported metal oxide material, its preparation method and application. Utilizing the natural hollow structure of cattail fluff fiber (inner diameter 5 - 20 μm, wall thickness 1 - 3 μm), which has the advantages of higher porosity and conductivity, a high specific surface area conductive network is formed after nitrogen and phosphorus doping. The reduction self-oxidation method (induced by sodium borohydride) is used to introduce oxygen vacancies on the surface of the metal oxide, reducing the reaction energy barrier. At the same time, through the construction of nitrogen and phosphorus doping and oxygen vacancies, the hydrophilicity of the material is significantly improved, and the prepared carbon-supported metal oxide material has excellent electrocatalytic oxygen evolution reaction performance.
[0009] To achieve the above object, the present invention is realized through the following technical solutions: A preparation method of a carbon-supported metal oxide material, comprising the following steps:
[0010] S1. Mix cattail fluff fiber with a dopant solution and perform impregnation to obtain element-doped cattail fluff fiber;
[0011] S2. Calcinate the element-doped cattail fluff fiber in an inert gas atmosphere to obtain element-doped biomass carbon;
[0012] S3. Mix the element-doped biomass carbon, nickel source, iron source, dispersant and water, and perform impregnation to obtain a biomass carbon-supported metal oxide precursor;
[0013] S4. Add a reducing agent to the biomass carbon-supported metal oxide precursor and perform a reduction self-oxidation reaction to obtain a carbon-supported metal oxide material.
[0014] Preferably, the dopant solution includes an aqueous solution of diammonium hydrogen phosphate; the mass ratio of the solute in the aqueous solution of diammonium hydrogen phosphate to the mass of cattail fluff fiber is (1 - 3):1.
[0015] Preferably, the impregnation temperature is (50 - 80) °C, with condensation reflux, and the impregnation time is (6 - 24) h.
[0016] Preferably, the inert gas is nitrogen or argon; the gas flow rate is (50 - 200) mL / min.
[0017] Preferably, the calcination temperature is (500 - 900) °C, the heating rate is (2 - 10) °C / min, and the holding time is (1 - 5) h.
[0018] Preferably, the nickel source is nickel chloride or nickel nitrate; the iron source is iron chloride or iron nitrate; the dispersant is polyethylene glycol or polyvinylpyrrolidone; the dosage ratio of the element-doped biomass carbon, nickel source, iron source and dispersant is (0.02 - 0.2) g : (2 - 0.5) mmol : (0.5 - 2) mmol : (0.1 - 1.0) g.
[0019] Preferably, the impregnation temperature is room temperature and the impregnation time is (6 - 24) h.
[0020] Preferably, the reducing agent is sodium borohydride or ascorbic acid; the dosage of the reducing agent is (0.02 - 0.5) g, which is dissolved in 20 mL of water.
[0021] Preferably, the reduction auto-oxidation reaction time is (3 - 12) h.
[0022] In the present invention, cattail fluff fibers are used as raw materials, and the cattail fluff fibers are impregnated and doped, and then roasted to be converted into nitrogen and phosphorus element-doped biomass carbon. Then, nickel-iron layered double metal hydroxides are in-situ grown on the surface of the biomass carbon through a reduction auto-oxidation reaction with iron nitrate and nickel nitrate. The doped elements introduced on the biomass carbon can improve the conductivity, structural stability and wettability of the material. Under the action of the dispersant polyethylene glycol, nickel and iron ions are evenly distributed on the biomass carbon. Then, the addition of the reducing agent sodium borohydride can convert nickel and iron ions into metal nanoparticles, and the metal nanoparticles continue to react with hydrated anions and auto-oxidize into layered double metal hydroxides. For the layered double metal hydroxides prepared by reduction auto-oxidation, since sodium borohydride can undergo a partial reduction reaction during the auto-oxidation process, reducing the high-valent metal ions to low-valent states and forming oxygen vacancies, the oxygen vacancies can change the surface charge distribution of the layered double metal hydroxides and improve the catalytic performance of the layered double metal hydroxides, making the prepared composite material have good hydrophilicity, conductivity, abundant active sites and good catalytic activity for the oxygen evolution reaction.
[0023] The present invention provides a carbon-supported metal oxide material, its preparation method and application. It has the following
[0024] Beneficial effects:
[0025] 1. By using natural biomass cattail fluff as a carbon source to prepare biomass carbon, the present invention can effectively reduce the preparation cost, and the tubular hollow structure of the cattail fluff fibers can provide a template for the growth of metal oxides.
[0026] 2. The present invention greatly improves the OER reaction performance of the catalyst through the dual-metal synergistic effect generated by Fe and Ni element doping.
[0027] 3. The present invention prepares a carbon-supported metal oxide electrocatalyst by using a redox self-oxidation method. The synthesis operation steps are simple and feasible, the reaction conditions are mild, the equipment requirements are low, it is green and environmentally friendly, the raw material sources are simple, the cost is low, the energy consumption is low, and it has a high tolerance for experimental parameters.
[0028] 4. The present invention helps to efficiently utilize biomass resources and conduct electrocatalytic reactions for oxygen evolution reactions, solves the problems of expensive traditional electrocatalytic materials, low catalytic activity, and high overpotential, etc., and can be applied to large-scale industrial promotion, and has practical application value in the field of electrocatalytic water splitting.
[0029] 5. The carbon-supported metal oxide disclosed in the present invention has an overpotential of only 192 mV at a current density of 10 mA·cm -2 which is far lower than that of the element-doped biomass carbon (338 mV) and metal oxide (275 mV) in the comparative example, and the Tafel slope is only 23.4 mV / dec, which is also far lower than that of the element-doped biomass carbon (47.6 mV) and metal oxide (76.5 mV) in the comparative example, having a lower starting potential and faster reaction kinetics.
[0030] 6. For the carbon-supported metal oxide material disclosed in the present invention, the biomass carbon source used in its synthesis is not limited to cattail fiber, and this research result provides an important reference for the subsequent research and preparation of biomass carbon-based OER catalysts. Description of the Drawings
[0031] Figure 1 SEM image of the element-doped biomass carbon material of Comparative Example 1;
[0032] Figure 2 SEM image of the metal oxide material of Comparative Example 2;
[0033] Figure 3 SEM image of the carbon-supported metal oxide material obtained in Example 1;
[0034] Figure 4 Contact angle of the element-doped biomass carbon material of Comparative Example 1;
[0035] Figure 5 Contact angle of the metal oxide material of Comparative Example 2;
[0036] Figure 6 Contact angle of the carbon-supported metal oxide material of Comparative Example 3;
[0037] Figure 7 Infrared spectrum of the materials obtained in Example 1 and Comparative Examples 1-2;
[0038] Figure 8 XRD pattern of the materials obtained in Example 1 and Comparative Examples 1-2;
[0039] Figure 9 Raman spectra of the materials obtained in Example 1 and Comparative Examples 1-2;
[0040] Figure 10 XPS spectrum of the carbon-supported metal oxide material obtained in Example 1;
[0041] Figure 11 Cyclic voltammetry test results of the materials obtained in Examples 1-8 and Comparative Examples 1-2 in a three-electrode system;
[0042] Figure 12 Electrochemical test results of the materials obtained in Example 1 and Comparative Examples 1-2 in a three-electrode system;
[0043] Figure 13 Electrochemical test results of the materials obtained in Examples 1-3 in a three-electrode system;
[0044] Figure 14 Electrochemical test results of the materials obtained in Example 1 and Examples 4-5 in a three-electrode system;
[0045] Figure 15 Electrochemical test results of the materials obtained in Example 1 and Examples 6-8 in a three-electrode system. Detailed implementation mode
[0046] The present invention provides a preparation method of a carbon-supported metal oxide material, comprising the following steps:
[0047] S1. Mix cattail fluff fibers with a doping agent solution, impregnate to obtain element-doped cattail fluff fibers;
[0048] S2. Bake the element-doped cattail fluff fibers in an inert gas atmosphere to obtain element-doped biomass carbon;
[0049] S3. Mix the element-doped biomass carbon, nickel source, iron source, dispersant and water, impregnate to obtain a biomass carbon-supported metal oxide precursor;
[0050] S4. Add a reducing agent to the biomass carbon-supported metal oxide precursor, carry out a reduction self-oxidation reaction to obtain a carbon-supported metal oxide material.
[0051] In the present invention, unless otherwise specified, the required preparation raw materials are all commercially available products well-known to those skilled in the art.
[0052] Mix cattail fluff fibers with a dopant solution and impregnate them to obtain element-doped cattail fluff fibers. In the present invention, the cattail fluff fibers are preferably picked during the period when the cattails are mature and the fluff is plump, and are successively subjected to seed removal, water washing and drying treatments: The present invention has no special limitation on the source of the cattail fluff fibers, and they can be obtained according to the sources well-known in the art. The present invention has no special limitation on the specific processes of picking and seed removal, and the cattail fluff fibers can be obtained according to the processes well-known in the art. The present invention has no special limitation on the water washing, as long as the impurities attached to the cattail fluff fibers can be removed. In the present invention, the drying temperature is preferably 40-80°C, more preferably 60°C.
[0053] In the present invention, the dopant solution includes an aqueous solution of diammonium hydrogen phosphate; the total mass of the solute and water in the aqueous solution of diammonium hydrogen phosphate is 100 g. In the present invention, the mass ratio of the solute to the mass of the cattail fluff fibers is preferably (1-3):1, more preferably 2:1. The present invention improves the structural stability of the cattail fluff fibers through doping liquid impregnation treatment and introduces nitrogen and phosphorus elements.
[0054] In the present invention, the impregnation temperature is preferably (50-80)°C, with condensation reflux, more preferably 60°C. The impregnation time is preferably (6-24) h, more preferably 10 h.
[0055] After the treatment is completed, the present invention preferably dries the obtained material at 60°C to obtain element-doped cattail fluff fibers; the present invention has no special limitation on the drying process, and it can be carried out according to the processes well-known in the art.
[0056] After obtaining the element-doped cattail fluff fibers, the present invention calcines the element-doped cattail fluff fibers in an inert gas atmosphere to obtain element-doped biochar. In the present invention, the inert gas is preferably nitrogen or argon, more preferably nitrogen; the present invention uses the inert gas as a protective gas to prevent the calcined product from contacting with oxygen and undergoing an oxidation reaction.
[0057] In the present invention, the gas flow rate of the inert gas is preferably (50-200) mL / min, more preferably 100 mL / min.
[0058] In the present invention, the calcination process preferably includes pre-oxidation by heating to 200°C at a rate of 2°C / min under room temperature conditions, holding for 1 h and then performing calcination. The calcination temperature is preferably (500-900)°C, more preferably 800°C; the heating rate is preferably (2-10)°C / min, more preferably 2°C; the holding time is preferably (1-5) h, more preferably 1 h. In the present invention, the calcination equipment is preferably a tube furnace.
[0059] In the present invention, the pre-oxidation treatment can remove impurities in the biomass and improve the carbonization efficiency; during calcination, an activation doping reaction occurs. Diammonium hydrogen phosphate decomposes under high-temperature conditions, and nitrogen and phosphorus elements vaporize and dope into the interior of the biomass carbon, which can enhance the chemical stability of the biomass carbon, improve the hydrophilic ability of the material to a certain extent, and prevent it from undergoing chemical changes or structural damage during the electrocatalysis process. By controlling the doping process and heat treatment conditions, the pore structure of the biomass carbon can be regulated to have a higher specific surface area and a more abundant pore structure.
[0060] After the calcination treatment is completed, the present invention preferably washes and dries the obtained material to obtain element-doped biomass carbon; the present invention has no special limitations on the washing and drying processes, and they can be carried out according to the processes well-known in the art.
[0061] After obtaining the element-doped biomass carbon, the present invention mixes the element-doped biomass carbon, nickel source, iron source, dispersant, and water, and performs impregnation to obtain a metal oxide precursor supported on biomass carbon. In the present invention, the nickel source is preferably nickel chloride or nickel nitrate, more preferably nickel nitrate; the iron source is preferably iron chloride or iron nitrate, more preferably iron nitrate; the present invention uses the nickel source and iron source to provide metal ions in the synthesis of bimetallic hydroxide.
[0062] In the present invention, the dispersant is preferably polyethylene glycol or polyvinylpyrrolidone, more preferably polyethylene glycol; the present invention uses the dispersant to change the surface properties of the element-doped biomass carbon, facilitate the uniform dispersion of metal ions, and maintain stability.
[0063] In the present invention, the dosage ratio of the element-doped biomass carbon, nickel source, iron source, dispersant, and water is preferably (0.02 - 0.2) g : (2 - 0.5) mmol : (0.5 - 2) mmol : (0.1 - 1.0) g : 100 mL; more preferably 0.1 g : 1.2 mmol : 0.8 mmol : 0.4 g : 100 mL.
[0064] In the present invention, the impregnation temperature is room temperature, and the impregnation time is preferably (6 - 24) h; more preferably 12 h, to obtain a metal oxide precursor supported on biomass carbon.
[0065] In the present invention, the impregnation process is preferably carried out under stirring conditions. The present invention has no special limitations on the stirring process, and the materials can be mixed evenly according to the processes well-known in the art.
[0066] A reducing agent is added to the biomass carbon-supported metal oxide precursor, and a reduction reaction is carried out to obtain a carbon-supported metal oxide material. In the present invention, the reducing agent is preferably sodium borohydride or ascorbic acid, more preferably sodium borohydride; the present invention utilizes the strong reducibility of sodium borohydride to reduce metal ions to metal nanoparticles, and a partial reduction reaction is carried out during the auto-oxidation of the metal nanoparticles to create oxygen vacancies, thereby improving the catalytic performance of the layered double metal hydroxide.
[0067] In the present invention, the dosage of the reducing agent is preferably (0.02 - 0.5) g, more preferably 0.1 g, and it is dissolved in 20 mL of water.
[0068] In the present invention, the reduction reaction process is preferably carried out under stirring conditions, and 20 mL of the reducing agent is added dropwise. The present invention has no special limitation on the stirring process, and the materials can be mixed evenly according to the process well-known in the art.
[0069] In the present invention, the auto-oxidation reaction time is preferably (3 - 12) h, more preferably 6 h.
[0070] After the auto-oxidation reaction is completed, the present invention preferably centrifuges and washes the obtained material, and dries it under vacuum conditions at 60 °C to obtain a carbon-supported metal oxide material; the present invention has no special limitation on the centrifugation and washing processes, and they can be carried out according to the process well-known in the art.
[0071] The present invention also provides the application of the above-described carbon-supported metal oxide material as an electrode material.
[0072] In the present invention, the application is preferably the application in the oxygen evolution reaction.
[0073] The present invention has no special limitation on the application of the electrode material in the oxygen evolution reaction, and the application well-known to those skilled in the art can be adopted.
[0074] To further illustrate the present invention, the following describes in detail a carbon-supported metal oxide material and its preparation method and application provided by the present invention in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts belong to the protection scope of the present invention.
[0075] Example 1
[0076] The present invention provides a preparation method of a carbon-supported metal oxide material, including the following steps:
[0077] Dissolve 20 g of diammonium hydrogen phosphate in 80 mL of water, add 10 g of cattail fluff fiber, stir to fully wet the cattail fluff fiber, heat the mixture to 60 °C, carry out condensation reflux, cool after keeping warm for 10 h, separate the solid matter and dry it at 60 °C to obtain element-doped cattail fluff fiber.
[0078] Under the condition that the protective gas is nitrogen and the flow rate is 100 mL / min, place the element-doped cattail fluff fiber in a porcelain boat, heat it to 200 °C at a rate of 2 °C / min in a tube furnace, keep it warm for 1 h, then continue to heat it to 800 °C and calcine it for 1 h. Wash and dry the obtained material to obtain element-doped biomass carbon.
[0079] Dissolve 1.2 mmol of nickel nitrate, 0.8 mmol of iron nitrate and 0.4 g of polyethylene glycol in 100 mL of water, add 0.1 g of the element-doped biomass carbon, and impregnate it for 12 h under stirring conditions to obtain a metal oxide precursor supported on biomass carbon.
[0080] Under stirring conditions, slowly add dropwise 20 mL of an aqueous solution containing 0.1 g of sodium borohydride to the metal oxide precursor supported on biomass carbon. After the addition of the solution is completed, continue to react for 6 h. Centrifuge, separate, wash and dry the obtained product to obtain a carbon-supported metal oxide material.
[0081] Example Two
[0082] The calcination temperature is 500 °C, and other technical means are the same as those in Example One to obtain the carbon-supported metal oxide material.
[0083] Example Three
[0084] The calcination temperature is 900 °C, and other technical means are the same as those in Example One to obtain the carbon-supported metal oxide material.
[0085] Example Four
[0086] The mass of the solute in the diammonium hydrogen phosphate solution is 10 g, and other technical means are the same as those in Example One to obtain the carbon-supported metal oxide material.
[0087] Example Five
[0088] The mass of the solute in the diammonium hydrogen phosphate solution is 30 g, and other technical means are the same as those in Example One to obtain the carbon-supported metal oxide material.
[0089] Example Six
[0090] The molar masses of nickel nitrate and iron nitrate are 0.16 mmol and 0.04 mmol respectively, and other technical means are the same as those in Example One to obtain the carbon-supported metal oxide material.
[0091] Example Seven
[0092] The molar masses of nickel nitrate and iron nitrate are 0.08 mmol and 0.12 mmol respectively. Other technical means are the same as those in Example 1, and the carbon-supported metal oxide material is obtained.
[0093] Example VIII
[0094] The molar masses of nickel nitrate and iron nitrate are 0.04 mmol and 0.16 mmol respectively. Other technical means are the same as those in Example 1, and the carbon-supported metal oxide material is obtained.
[0095] Comparative Example I
[0096] Dissolve 20 g of diammonium hydrogen phosphate in 80 mL of water, add 10 g of cattail fluff fiber, stir to fully wet the cattail fluff fiber, heat the mixture to 60 °C, carry out condensation reflux, keep warm for 10 h and then cool, separate the solid matter and dry it at 60 °C to obtain element-doped cattail fluff fiber.
[0097] Under the condition that the protective gas is nitrogen and the flow rate is 100 mL / min, place the element-doped cattail fluff fiber in a porcelain boat, heat it to 200 °C at a rate of 2 °C / min in a tube furnace, keep it warm for 1 h, and then continue to heat it to 800 °C and calcine it for 1 h. Wash and dry the obtained material to obtain element-doped biomass carbon.
[0098] Comparative Example II
[0099] Dissolve 1.2 mmol of nickel nitrate, 0.8 mmol of iron nitrate and 0.4 g of polyethylene glycol in 100 mL of water. Dropwise add 20 mL of an aqueous solution containing 0.1 g of sodium borohydride under stirring conditions. After the solution is added dropwise, continue to react for 6 h. Centrifuge, separate, wash and dry the obtained product to obtain a metal oxide material.
[0100] Material Characterization
[0101] Perform a scanning electron microscope test on the element-doped biomass carbon of Comparative Example I. The obtained SEM image is shown in Figure 1 . It can be seen from Figure 1 that after the cattail fluff fiber is doped with nitrogen and phosphorus elements and calcined at 800 °C, it can still better maintain the hollow tubular structure and the surface is smooth.
[0102] Perform a scanning electron microscope test on the metal oxide material of Comparative Example II. The obtained SEM image is shown in Figure 2 . It can be seen from Figure 2 that the metal oxide material of Comparative Example II is distributed in a dense and orderly manner, forming a closely connected framework. This three-dimensional network structure not only increases the specific surface area of the material, but also provides it with rich active sites and channels, which is beneficial to the material transport and the progress of the reaction process.
[0103] The carbon-supported metal oxide material of Example 1 was tested by scanning electron microscopy, and the obtained SEM image is shown in Figure 3 . As can be seen from Figure 3 , after the element-doped biomass carbon material was impregnated with nickel and iron ions in a certain proportion and underwent a reduction self-oxidation process, a layer of metal oxide was in-situ grown on the surface of the material. The biomass carbon material itself has good electrical conductivity, which is mainly due to its unique carbonaceous structure and electron transport ability. The pore structure of the biomass carbon provides sufficient attachment space for the catalyst, enabling the catalyst particles to be evenly dispersed on the surface of the substrate. The layered double metal hydroxide exhibits excellent catalytic performance and a low overpotential in the alkaline OER reaction. By forming an effective electron transport network with the biomass carbon, it helps the ions and electrons participating in the oxygen evolution reaction to be adsorbed and diffused faster from the electrolyte solution, improving the overall catalytic ability of the element-doped biomass carbon material.
[0104] The contact angle of the element-doped biomass carbon of Comparative Example 1 was tested, and the obtained contact angle value is shown in Figure 4 . As can be seen from Figure 4 , after the cattail fluff fiber was doped with nitrogen and phosphorus elements and calcined at 800 °C, the contact angle was 147°. This material shows obvious hydrophobicity, which is not conducive to the wetting of the electrolyte on its surface.
[0105] The contact angle of the metal oxide material of Comparative Example 2 was tested, and the obtained contact angle value is shown in Figure 5 . As can be seen from Figure 5 , the contact angle of the metal oxide obtained by co-reducing and self-oxidizing the bimetallic ions after being dispersed by a dispersant is 78°. This indicates that the material has good hydrophilicity, which can promote the wetting of the electrolyte on its surface, thus being beneficial to improving the catalytic performance of the material.
[0106] The contact angle of the carbon-supported metal oxide material in Example 1 was tested, and the results are as shown in Figure 6 . As can be seen from Figure 6 , when the liquid droplet contacts the surface of the material, the liquid droplet immediately penetrates. After the co-reduction self-oxidation process, a uniform layer of metal oxide is formed on the surface of the element-doped biomass carbon material. The oxide spreads on the surface of the material, significantly enhancing the hydrophilicity of the composite material compared to Comparative Example 1 and Comparative Example 2, thereby promoting the rapid adsorption and diffusion of relevant ions between the material surface and the electrolyte solution in the oxygen evolution reaction. This improved hydrophilic property further enhances the catalytic efficiency of the material, enabling the element-doped biomass carbon material to exhibit better performance in the overall catalytic reaction.
[0107] The carbon-supported metal oxide material, element-doped biomass carbon material, and metal oxide material used in Example 1, Comparative Example 1, and Comparative Example 2 were respectively analyzed by infrared spectroscopy, and the obtained results are shown in Figure 7 . As can be seen from Figure 7It can be seen that at 3418 cm -1 is the stretching vibration of OH - At 2921 cm -1 and 2845 cm -1 are the stretching vibrations of C-H. At 2845 cm -1 is also the stretching vibration of C-H. The weak stretching vibration near 1455 cm -1 is attributed to the H-O-H bending vibration of interlayer water. The absorption peak at 1375 cm -1 can be attributed to the bending vibration of OH - in the layered double hydroxide. Since the biomass carbon contains abundant functional groups that will interact with OH - and thus change or mask the bending vibration mode of OH - in the spectrum of the carbon-supported metal oxide. The peak at 1150 - 1060 cm -1 can be attributed to the characteristic peak of C-O-C vibration. The band at about 674 cm -1 is attributed to the M-O vibration, where M represents iron and nickel atoms in the hydroxide. The OH -1 stretching vibration of the biomass carbon is weak at 3418 cm - . After in-situ growth of the layered double metal oxide, the OH - stretching vibration has a wide and strong absorption band, indicating that the adsorption capacity of the material surface for OH - is enhanced, and the electrocatalytic process is easier to proceed, thus improving the catalytic activity.
[0108] XRD tests were respectively carried out on the carbon-supported metal oxide material, element-doped biomass carbon material, and metal oxide material used in Example 1, Comparative Example 1, and Comparative Example 2, and the obtained results are shown in Figure 8 . It can be seen from Figure 8 that the element-doped biomass carbon shows a diffraction peak at 2θ = 21.2°, and this biomass carbon is an amorphous carbon material. The metal oxide shows diffraction peaks at 34.3° and 60.9°, corresponding to the (012) crystal plane and (110) crystal plane in PDF#40 - 0215. In addition to the diffraction peaks at 2θ = 21.2°, 34.3°, and 60.9°, the carbon-supported metal oxide also shows a diffraction peak at 12.0°, corresponding to the (003) crystal plane in PDF#40 - 0215. The diffraction peak intensity of the carbon-supported metal oxide at 2θ = 21.2° is weaker than that of the biomass carbon because the surface structure changes after in-situ growth of the metal oxide on the biomass carbon surface. The appearance of a new diffraction peak at 12.0° indicates that the growth of the metal oxide on the biomass carbon surface is more conducive to the exposure of the (003) crystal plane.
[0109] Raman tests were respectively conducted on the carbon-supported metal oxide materials, element-doped biomass carbon materials, and metal oxide materials used in Example 1, Comparative Example 1, and Comparative Example 2. The obtained results are shown in Figure 9 . As can be seen from Figure 9 , the peak at 469 cm -1 can be attributed to the eg1 bending vibration of NiⅡ-OH in brucite-like layered double metal hydroxides, and the peak at 683 cm -1 can be attributed to the a1g bending vibration of NiⅡO-H. The D peak (disorder or defect band) and G peak (crystalline graphite band) of the carbon-supported metal oxide and element-doped biomass carbon appear at Raman shifts of 1340 cm -1 and 1591 cm -1 respectively. All samples show that the content of the D peak is higher than that of the G peak, indicating the existence of a large number of sp3-bonded carbon atoms; the intensity ratio (ID / IG) is calculated to be 1.03 for all, which also shows that more defects are formed in the carbon material skeleton.
[0110] XPS test was conducted on the carbon-supported metal oxide material of Example 1. The obtained results are shown in Figure 10 . Figure 10 In , a is the fine structure spectrum of C1 s, b is the fine structure spectrum of N1 s, c is the fine structure spectrum of O1 s, d is the fine structure spectrum of P2p, e is the fine structure spectrum of Ni2p, and f is the fine structure spectrum of Fe2p. Figure 10 In a, the C1 s spectrum is fitted by 3 peaks, located at 284.6±0.1 eV, 286.4±0.1 eV, and 288.8±0.1 eV, representing C-C, C-O / C-N, and C=O respectively. In addition to the carbon-carbon bond, it also shows the combination with other elements, and the oxygen functional group can improve the surface hydrophilicity. Figure 10 In b, the N1 s spectrum is fitted by 4 peaks, located at 398.4±0.1 eV, 399.3±0.1 eV, 400.0±0.1 eV, and 402.7±0.1 eV, representing -C=N, -C-N-, pyrrole / pyridone-N, and quaternary ammonium-N respectively. These C=N / C-N– bonds crosslinked with C=O and C=C– contribute to the transformation of the linear structure into a cyclic structure through polymerization, oxidative cyclization, and random fracture reactions, thus forming a more stable biomass carbon structure. Pyridone-N is a six-membered ring composed of C atoms, in which the sp2 hybridized N atom has a pair of lone electrons, which can bring a Pπ electron to the graphite system; while pyrrolone-N belongs to a five-membered ring composed of C atoms and has two pairs of lone electrons. Both pyridone-N and pyrrolone-N have relatively high redox reaction activities. Quaternary ammonium-N is also called graphite N. The N atom added to the graphene hexagonal ring can contribute two Pπ electrons to the graphite system, thus promoting the charge transfer rate at the electrode / electrolyte interface. Figure 10In c, the O 1s spectrum is fitted with five peaks located at 529.7 ± 0.1 eV, 530.6 ± 0.1 eV, 531.3 ± 0.1 eV, 532.0 ± 0.1 eV, and 532.8 ± 0.1 eV, which are denoted as Fe-O, Ni-O / C=O / P=O, O-C / P-O-C, C-OH / P-OH, and O-C=O, respectively. Thus, a large number of oxygen-containing functional groups and metal oxides are determined to exist in the material. The heteroatoms in the carbon framework can change the electronic structure and charge distribution of adjacent carbon atoms, thereby promoting the adsorption of reaction intermediates and improving the water electrolysis performance. Figure 10 In d, the P 2p spectrum is fitted with three peaks located at 132.3 ± 0.1 eV, 132.8 ± 0.1 eV, and 133.8 ± 0.1 eV, which are denoted as C3-PO group, C2-P02 group, and C-O-P bond, respectively. The formation of C-O-P can not only disperse the electron perturbation but also play a bridging role to prevent the shrinkage of the pores of the biomass carbon and the collapse of the hollow structure. Figure 10 In e, the Ni 2p spectrum is fitted with four doublets. Taking the side with lower binding energy as an example, they are located at 855.7 ± 0.1 eV, 856.9 ± 0.1 eV, 861.6 ± 0.1 eV, and 864.9 ± 0.1 eV, which are denoted as the satellite peaks of Niδ+p3 / 2, Ni2+p3 / 2, Ni3+p3 / 2, and Nip3 / 2, respectively. The other side is the p1 / 2 peak. Figure 10 In f, the Fe 2p spectrum is fitted with four doublets. Taking the side with lower binding energy as an example, they are located at 705.7 ± 0.1 eV, 709.7 ± 0.1 eV, 712.2 ± 0.1 eV, and 718.5 ± 0.1 eV, which are denoted as the satellite peaks of Feδ+p3 / 2, Fe2+p3 / 2, Fe3+p3 / 2, and Fep3 / 2, respectively. The other side is the p1 / 2 peak.
[0111] Performance test
[0112] The performance results of the electrocatalytic composite material are obtained using a CH Instrument CHI760E electrochemical workstation with a three-electrode test system.
[0113] The three-electrode system consists of a self-made electrode (working electrode), a silver / silver chloride electrode (reference electrode), a platinum plate electrode (counter electrode), and an electrolyte. The potential conversion formula between the silver / silver chloride electrode and the reversible hydrogen electrode (RHE) is: ERHE = EAg / AgCl + 0.0591×pH + 0.197.
[0114] Preparation of the working electrode. First, weigh 8 mg of the example sample / control sample, then weigh 1 mg of polyvinylidene fluoride and 1 mg of acetylene black. Place the three in an agate mortar, and then drop 0.1 mL (3 - 4 drops) of N-methyl-2-pyrrolidone. Grind evenly until the mixture forms a homogeneous paste. Use a small brush to dip the paste and coat it on one side of the pre-weighed 1×1 cm 2 nickel foam, transfer it to a blast drying oven and dry it at 60 °C for 24 h, then weigh it. Calculate the mass of the loaded material according to the mass change of the nickel foam, and keep the loading amount within the range of 1 - 3 mg. Finally, press it into an electrode sheet under a pressure of 10 MPa using a tablet press.
[0115] Install a three-electrode test system, and the electrolyte is 1 M NaOH. Fix the self-made electrode with an electrode clip to ensure that the area of the sample immersed in the liquid surface is 1.0 cm 2 , and then start the test. Activate the electrocatalytic composite material using cyclic voltammetry (CV) with a scan rate of 10 mV·s -1 , until the curves basically overlap, indicating that the activation is completed. Perform CV tests at scan rates of 10, 20, 30, 50, 70, and 100 mV / s respectively, and then start the test of linear sweep voltammetry (LSV). To avoid the overlap of the oxidation peak and the OER signal peak during the positive sweep, scan at a scan rate of 5 mV / s in the potential range of -0.1 - 0.9 V to obtain the LSV curve. The double-layer capacitance (Cd l) is measured in the non-Faradaic region (0.25 V - 0.35 V vs. Ag / AgCl) by performing CV tests at different scan rates. Take the scan rate as the abscissa and the difference between the middle values of the potential interval divided by two as the ordinate, and the slope obtained after fitting is the double-layer capacitance. Electrochemical impedance spectroscopy (EIS) test analysis is used to evaluate the charge transfer ability of the material, which is carried out at a frequency from 100000 Hz to 0.01 Hz and an amplitude of 10 mV.
[0116] Perform CV tests in the non-Faradaic region on the materials obtained from Example 1 to Example 8 and Comparative Example 1 to Comparative Example 2, and the obtained results are shown in Figure 11 . From Figure 11 , it can be seen that for the materials of Example 1 to Example 8 and Comparative Example 1 to Comparative Example 2 in the non-Faradaic region, since there is no chemical change caused by the transfer of charge between the electrode and the electrolyte, the current mainly comes from the charging and discharging processes of the double layer, and the CV curve presents a shape close to a rectangle. As the scan rate increases, the current density at the same bias voltage also gradually increases.
[0117] Perform electrocatalytic performance tests on the materials obtained from Example 1, Comparative Example 1, and Comparative Example 2, and the obtained results are shown in Figure 12 . From Figure 12 a, it can be seen that when the current density is 10 mA·cm -2At this time, the overpotentials of Comparative Example 1 and Comparative Example 2 were 338 mV and 275 mV respectively, while the overpotential of the metal oxide supported on carbon in Example 1 was 192 mV, indicating that in-situ growth of metal oxides on the surface of element-doped biomass carbon can effectively reduce the overpotential of the material. From Figure 12 As shown in b, the Tafel slopes of Comparative Example 1 and Comparative Example 2 were 47.6 mV / dec and 76.5 mV / dec respectively, while the Tafel slope of Example 1 was 23.4 mV / dec. The Tafel slope describes the relationship between the rate constant of the charge transfer reaction and the electrode potential in the electrochemical process. The smaller the Tafel slope, the smaller the logarithmic change of the current density at the same overpotential, that is, the faster the current density increases with the increase of the overpotential. This indicates that the charge transfer ability of element-doped biomass carbon is better than that of metal oxides, and the coupling of the two can further improve the charge transfer ability. From Figure 12 As shown in c, the double-layer capacitance (Cdl) can be obtained by processing the CV test data in the non-Faraday region. Example 1 has a higher Cdl. From Figure 12 As shown in d, after loading metal oxides, the low contact angle, high specific surface area, and oxygen vacancies of element-doped biomass carbon can cooperate to reduce the charge transfer impedance and improve the OER activity.
[0118] The electrocatalytic performance of the materials obtained in Examples 1 to 3 was tested, and the results are shown in Figure 13 . From Figure 13 As shown in a, when the current density was 10 mA·cm -2 , the overpotentials of Examples 1 to 3 were 192 mV, 287 mV, and 215 mV respectively, indicating that regulating the calcination temperature is beneficial to reducing the overpotential when preparing element-doped biomass carbon. From Figure 13 As shown in b, too high a calcination temperature will damage the internal structure of biomass carbon and reduce the charge transfer ability. From Figure 13 As shown in c and 10d, high-temperature calcination can improve the carbonization degree of the material, increase Cdl, and reduce the internal resistance of the material.
[0119] The electrocatalytic performance of the materials obtained in Example 1, Example 4, and Example 5 was tested, and the results are shown in Figure 14 . From Figure 14 As shown in a, when the current density was 10 mA·cm -2 , the overpotentials of Example 1, Example 4, and Example 5 were 192 mV, 260 mV, and 212 mV respectively, indicating that increasing the doping amount of nitrogen and phosphorus elements is beneficial to reducing the overpotential when preparing element-doped biomass carbon. Figure 14 b, c, and d can correspond to a.
[0120] The electrocatalytic performance of the materials obtained in Example 1, Example 6 and Example 8 was tested, and the results are shown in Figure 15 . It can be seen from Figure 15 that when the current density is 10 mA·cm -2 , the overpotentials of Example 1, Example 6 and Example 8 are 192 mV, 276 mV, 289 mV and 290 mV respectively, and the Tafel slope, Cd l and EIS also show a similar trend of change in ability. This is because the different Ni:Fe ratios will affect the number and distribution of active sites of the material. When Ni:Fe = 3:2, the active sites may be more dense and evenly distributed, which helps to improve the OER performance. As the iron doping amount increases, the number of transferred electrons for the redox transition becomes smaller, which is related to the chemically induced phase transition behavior of the material under alkaline conditions.
[0121] Although the embodiments of the present invention have been shown and described, it will be understood by those of ordinary skill in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a carbon-supported metal oxide material, characterized in that: The following steps are involved: S1. The cattail fluff fiber is mixed with a doping agent solution and impregnated to obtain an element-doped cattail fluff fiber; S2. calcining the element-doped cattail fibers in an inert gas atmosphere to obtain element-doped biochar; S3. mixing the element-doped biochar, a nickel source, an iron source, a dispersant and water, and impregnating the mixture to obtain a biochar-loaded metal oxide precursor; S4. Adding a reducing agent to the biomass carbon-supported metal oxide precursor to carry out reduction-autooxidation reaction to obtain a carbon-supported metal oxide material.
2. The method for preparing a carbon-supported metal oxide material according to claim 1, characterized in that: The dopant solution includes a diammonium phosphate aqueous solution; the mass ratio of the solute mass in the diammonium phosphate aqueous solution to the cattail fiber is (1-3):
1.
3. The method for preparing a carbon-supported metal oxide material according to claim 1, characterized in that: The immersion temperature is (50-80)°C, condensation reflux, and the immersion time is (6-24) hours.
4. The method for preparing a carbon-supported metal oxide material according to claim 1, characterized in that: The inert gas is nitrogen or argon; the gas flow rate is (50-200) mL / min.
5. The method for preparing a carbon-supported metal oxide material according to claim 1, characterized in that: The calcination temperature is (500-900)°C, the heating rate is (2-10)°C / min, and the heat preservation time is (1-5)h.
6. The method for preparing a carbon-supported metal oxide material according to claim 1, characterized in that: The nickel source is nickel chloride or nickel nitrate; the iron source is ferric chloride or ferric nitrate; the dispersant is polyethylene glycol or polyvinyl pyrrolidone; the dosage ratio of the element-doped biochar, the nickel source, the iron source and the dispersant is (0.02-0.2) g: (2-0.5) mmol: (0.5-2) mmol: (0.1-1.0) g.
7. The method for preparing a carbon-supported metal oxide material according to claim 1, characterized in that: The immersion temperature is room temperature, and the immersion time is (6 to 24) hours.
8. The method for preparing a carbon-supported metal oxide material according to claim 1, characterized in that: The reducing agent is sodium borohydride or ascorbic acid; the reducing agent is used in an amount of (0.02-0.5) g, dissolved in 20 mL of water.
9. The method for preparing a carbon-supported metal oxide material according to claim 1, characterized in that: The reduction-autooxidation reaction time is (3-12) hours.
10. The carbon-supported metal oxide material prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing biomass carbon-based composite energy storage material by utilizing plant fiber
CN103332677A
Supercapacitor electrode materials based on plant fiber base and preparation method thereof
CN105845451A